Connecting Social Science and Information Technology through an Interface-Centric Framework of Analysis. - Sundström, Mikael ; 0000-0001-8711-6636 (Journal of Systemics, Cybernetics and Informatics, 2008)
The gathering pace of IT innovation has, or ought to have had notable methodological repercussions for the social-science community (and beyond). Where yesterday the researcher could unhurriedly unlock the social-scientific significance of a chosen medium, secure in the knowledge that his or her work would have bearing for many years, by now there is every reason to confront a fear that the prodded IT implementation may in fact be gone or at least heavily altered by the time such comprehensive research is concluded. This paper will propose a complementing systematic “interface-centric” research model capable of interconnecting a non-finite variety of IT implementations and social science studies in a coherent way. The paper also outlines how users “downstream”, whether political actors or technology operators can use the proposed framework to more easily approach and weight academic input when evaluating complex IT effects.
Keywords: Dimensions; Analysis; IT